Modern management tools in the latest models of socio-economic development - Buniak, Nadiia; Mylko, Inna; Onofriichuk, Liliia; Sak, Tetiana; Levytskyi, Viktor; Lukianova, Valentina; Tsymbaliuk, Irina; Pavlikha, Natalia; Cherchуk, Larysa; Khumarova, Nina; Popyk, Oleh; Jarosh, Piotr; et al. (Higher School of Social and Economic, 2023)
The monograph is dedicated to modern management tools in the context of the development of innovative, inclusive, green, and behavioral economies. It explores issues such as creative management, digital marketing, sustainable development, and brand strategy in today’s business environment. The publication unites scientific approaches to forming effective management strategies amid global challenges.
Keywords: Modern management tools; models of socio-economic development